Acquired cystic fibrosis transmembrane conductance regulator dysfunction. Issue 3 (1st September 2018) - Banks, Catherine; Freeman, Laura; Cho, Do Yeon; Woodworth, Bradford A.
Abstract : Sinonasal respiratory epithelium is a highly regulated barrier that employs mucociliary clearance (MCC) as the airways first line of defense. The biological properties of the airway surface liquid (ASL), combined with coordinated ciliary beating, are critical components of the mucociliary apparatus. The ASL volume and viscosity is modulated, in part, by the cystic fibrosis transmembrane conductance regulator (CFTR). The CFTR is an anion transporter of chloride (Cl − ) and bicarbonate (HCO3 − ) that is located on the apical surface of respiratory epithelium and exocrine glandular epithelium. Improved understanding of how dysfunction or deficiency of CFTR influences the disease process in both genetically defined cystic fibrosis (CF) and acquired conditions has provided further insight into potential avenues of treatment. This review discusses the latest data regarding acquired CFTR deficiency and use of CFTR specific treatment strategies for CRS and other chronic airway diseases.